Degradation and biodegradation of polyethylene with pro‐oxidant aditives under compost conditions establishing relationships between physicochemical and rheological parameters. Issue 43 (3rd August 2015) - Roé‐Sosa, Adriana; Estrada, Mirna R.; Calderas, Fausto; Sánchez-Arévalo, Francisco; Manero, Octavio; de Velasquez, María Teresa Orta L.
ABSTRACT In the present work, an analysis is carried out to provide a relationship between the Molecular Weight (Mw) of degraded LDPE films (containing Mn stearate as pro oxidant (MnSt‐LDPE) and changes in viscosity, elongation at break (EB %) and carbonyl index (CI) occurring during thermal degradation in the thermophilic phase of the compost process. The thermal treatment comprised various temperatures (50°C, 60°C, and 70°C) and exposure times, and was characterized through a so‐called Energy‐Time Factor (the product of thermal energy and exposure time). Changes in viscosity, EB %, and CI were correlated to this factor. A modified Mark‐Houwink equation was used to relate the zero shear‐rate viscosity and Mw of the degraded LDPE films. Results indicate that the EB %, Mw and viscosity decrease simultaneously with an increase in the CI as the Energy‐Time Factor augments, allowing the assessment of the variation of these properties with Mw. Calculations of the percentage abiotic degradation (%D) of LDPE films indicate that a Mw of 6 kg mol−1 corresponds to a maximum abiotic degradation degree of 91.85%, which is henceforth susceptible to biodegradation. The film treated with Energy‐Time Factor of 2.79E+09 J s mol−1 reached a 74% of biodegradation in 90 days (average time of the composting process). Results exhibit clearly the correlation between abiotic and biotic degradation. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42721.